Pegylated and liposomal doxorubicin is associated with high mortality and causes limited cardiotoxicity in mice - Christoffer Stark; Pekka Taimen; Timo Savunen; Juha Koskenvuo (BioMed Central Ltd., 2022)
Objective: We wanted to determine the impact of different doses of a pegylated and liposomal formulation of the cardiotoxic drug doxorubicin on cardiac function, fibrosis and survival in mice. The drug causes myocardial damage by producing reactive oxygen species, mitochondrial damage and lipid peroxidation. Thymosin beta 4 is a peptide with cardioprotective, anti-oxidant and anti-fibrotic properties and we further investigated whether the peptide could attenuate this drug-induced injury by measuring cardiac function and fibrosis.
Results: Mice receiving high doses of doxorubicin died early during follow-up. Lowering the dose improved survival but did not markedly impair cardiac function on echocardiography and caused only limited fibrosis on histology. Thymosin beta 4 had only a mild protective effect on early cardiac function and did not significantly influence myocardial fibrosis. In conclusion, the use of pegylated and liposomal doxorubicin was not appropriate for inducing experimental cardiomyopathy. Thymosin beta 4 therapy was not beneficial in this setting.